2023
DOI: 10.5435/jaaos-d-21-01055
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Comorbidities Associated With Early Mortality in Hip Fracture Patients: A Multicenter Study

Abstract: Objective:Multiple comorbidities in hip fracture patients are associated with increased mortality and complications. The goal of this study was to characterize the relationship between specific patient factors including comorbidities and outcomes in geriatric hip fractures, including length of stay, unplanned ICU admission, discharge disposition, complications, and mortality.Methods:This is a retrospective review of a trauma database from five Level 1 and Level 2 trauma centers of patients with hip fractures o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
3
1
Order By: Relevance
“…In a systematic review and meta-analysis by Ma et al the rate of early mortality following intertrochanteric fracture was 15.1% 36 . The in-hospital mortality rate reported in the literature ranged from 1.2 to 1.8%, which is lower than the mortality rate of our study (3.23%) 8 , 37 , 38 . It is worth noting that our hospital is a referral center, and our patients mainly come from regions with poor economic and sanitary conditions.…”
Section: Discussioncontrasting
confidence: 88%
“…In a systematic review and meta-analysis by Ma et al the rate of early mortality following intertrochanteric fracture was 15.1% 36 . The in-hospital mortality rate reported in the literature ranged from 1.2 to 1.8%, which is lower than the mortality rate of our study (3.23%) 8 , 37 , 38 . It is worth noting that our hospital is a referral center, and our patients mainly come from regions with poor economic and sanitary conditions.…”
Section: Discussioncontrasting
confidence: 88%
“…However, a previous Australian study found that the most common type of hip fractures was at the neck of the femur (56%) and pertrochanteric (or intertrochanteric) fractures (38%) [ 7 ]. We did not investigate individual comorbidities, which may be associated with higher risk of mortality following hip fracture [ 48 , 49 ]. Future research on individual comorbidities is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…In their multicenter study, McHugh et al 20 determined that diabetes and dementia affected mortality in all processes, while COPD was the only disease associated with in-hospital mortality. In a study of 911 deceased patients, Barcelo et al 21 found that 146 of them had CHF and 126 had dementia.…”
Section: Discussionmentioning
confidence: 99%